UNIFICATION OF THE LEGISLATION OF SOCIAL PROTECTION OF THE MILITARY SERVANTS OF THE ARMED FORCES OF UKRAINE AND PERSONS EQUALIZED TO THEM - Shkuropatskyi , Oleksandr; Artiushenko , Oleksandr (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2021)
ANNOTATION: the Paper is devoted to the study of the problem of systematization of legislation in the field of social protection of servicemen of the Armed Forces of Ukraine. It is noted that the system of social protection of servicemen of the Armed Forces of Ukraine and its legal regulation are chaotic, and do not have a proper conceptual sense. The main directions of reform are analyzed, in particular, adjustment of the content of social and control; systematization and codification of protection of military personnel; improvement of the mechanism for ensuring such social protection legislation on social protection of military personnel; the main problems of reform are highlighted. Significant influence of the political components, to regulate the social protection of servicemen, particularly by the Government can in the implementation of delegated authority, and the consequences of such influence on the implementation of the social rights of servicemen. The interaction of General and special rights of military personnel in the field of social protection is analyzed from the point of view of lack of systematization and inconsistency of legal regulation of such rights of military personnel of the Armed Forces of Ukraine and the mechanism for their implementation. In the article the conclusion about necessarity of creation of a Code of social protection of the military personnel of the Armed forces of Ukraine was made. The purpose of Code of social protection of the military personnel of the Armed forces of Ukraine is not only to systematize, but also to establish a mechanism for effective regulation and ensuring the implementation of both General and special social rights of military personnel of the armed forces of Ukraine. The General structure of the Code, and the main thematic areas for the content of its sections, as well as mandatory components that determine the mechanism of its action, are proposed.